Aplikasi Tiktok Sebagai Media Promosi Usaha Kuliner Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Riau - Pratama, Ichsan Yoga; Yusuf, Yusmar (CV. Rayyan Dwi Bharata, 2025)
The development of digital technology has had a significant impact on the business world, including the culinary sector. TikTok, as one of the social media platforms with rapid user growth, offers opportunities for entrepreneurs, includin7g students, to promote their products more widely and interactively. This research aims to analyze the utilization of TikTok as a promotional medium for culinary businesses among students of the Faculty of Economics and Business (FEB) at Riau University (UNRI). The research method used is a descriptive qualitative approach, with data collection techniques involving in-depth interviews and observations. The results indicate that TikTok plays an important role in enhancing the visibility of student culinary businesses through its interactive features, although there are challenges in creating engaging content and the platform's ever-changing algorithms. Therefore, effective marketing strategies are needed to optimize the use of TikTok in culinary promotion